The murine retinal pigment epithelium requires peroxisomal β-oxidation to maintain lysosomal function and prevent dedifferentiation - Kocherlakota, Sai; Das, Yannick; Swinkels, Daniëlle; Vanmunster, Maarten; Callens, Manon; Vinckier, Stefan; Vaz, Frédéric M.; Sinha, Debasish; Van Veldhoven, Paul P.; Fransen, Marc; Baes, Myriam (Proceedings of the National Academy of Sciences - PNAS, 2023)
Retinal pigment epithelium (RPE) cells have to phagocytose shed photoreceptor outer segments (POS) on a daily basis over the lifetime of an organism, but the mechanisms involved in the digestion and recycling of POS lipids are poorly understood. Although it was frequently assumed that peroxisomes may play an essential role, this was never investigated. Here, we show that global as well as RPE-selective loss of peroxisomal β-oxidation in multifunctional protein 2 (MFP2) knockout mice impairs the digestive function of lysosomes in the RPE at a very early age, followed by RPE degeneration. This was accompanied by prolonged mammalian target of rapamycin activation, lipid deregulation, and mitochondrial structural anomalies without, however, causing oxidative stress or energy shortage. The RPE degeneration caused secondary photoreceptor death. Notably, the deterioration of the RPE did not occur in an Mfp2/rd1 mutant mouse line, characterized by absent POS shedding. Our findings prove that peroxisomal β-oxidation in the RPE is essential for handling the polyunsaturated fatty acids present in ingested POS and shed light on retinopathy in patients with peroxisomal disorders. Our data also have implications for gene therapy development as they highlight the importance of targeting the RPE in addition to the photoreceptor cells.